Investigation of Antibacterial Susceptibility of Ag-Doped Oxide Coatings onto AZ91 Magnesium Alloy by Microarc Oxidation Method - Ebru Emine Sukuroglu (Advances in Materials Science and Engineering)
This study is focused on enhancing surface characteristics of AZ91 alloy with the microarc oxidation (MAO) method and bringing in antibacterial susceptibility to it. It is aimed to bring in antibacterial effect of silver (Ag) to AZ91 magnesium base materials covered with the MAO method. The structural and chemical compositions of the coating were analysed by using XRD, SEM, and EDS. In order to analyse antibacterial susceptibilities and bacteria adhesions, bacteria are marked using crystal violet in antibacterial efficacy tests. Susceptibility of coatings to Staphylococcus aureus (S. aureus-ATCC 29213) bacteria having high adhesion is analysed. In the study, it is concluded that the silver-containing coatings have a lot poor bacterial susceptibility than silver-free coatings, and noncoated samples have very strong bacterial susceptibilities. When the antimicrobial activity of the samples coated on silver-containing electrolyte is evaluated (zone diameter ∼40 mm), it is found as sensitive. Antimicrobial activity of samples coated in silver-free electrolyte is found as medium-sensitive (zone diameter ∼15 mm), and uncoated samples are observed to form any zones against bacterial infection.